Quantitation of Benzo[a]pyrene Metabolic Profiles in Human Bronchoalveolar H358) Cells by Stable Isotope Dilution Liquid Chromatography-Atmospheric Chemical Ionization Mass Spectrometry - Lu, Ding (2011)
Polycyclic aromatic hydrocarbons (PAHs) are ubiquitous environmental pollutants and are carcinogenic in multiple organs and species. Benzo[a]pyrene (B[a]P) is a representative PAH and has been studied extensively for its carcinogenicity and toxicity. B[a]P itself is chemically inert and requires metabolic activation to exhibit its toxicity and carcinogenicity. Three major metabolic pathways have been well documented. The signature metabolites generated from the radical cation (peroxidase or monooxygenase mediated) pathway are B[a]P-1,6-dione and B[a]P-3,6-dione, the signature metabolite generated from the diol-epoxide (P450 mediated) pathway is B[a]P-r-7,t-8,t-9,c-10-tetrahydrotetrol (B[a]P-tetrol-1) and the signature metabolite generated from the o-quinone (aldo-keto reductase mediated) pathway is B[a]P-7,8-dione. The contributions of these different metabolic pathways to cancer initiation and the exploitation of this information for cancer prevention are still under debate. With the availability of a library of [(13)C(4)]-labeled B[a]P metabolite internal standards, we developed a sensitive stable isotope dilution atmospheric pressure chemical ionization tandem mass spectrometry method to address this issue by quantitating B[a]P metabolites from each metabolic pathway in human lung cells. This analytical method represents a 500 fold increased sensitivity compared with a method using HPLC-radiometric detection. The limit of quantitation (LOQ) was determined to be 6 fmol on column for 3-hydroxybenzo[a]pyrene (3-OH-B[a]P), the generally accepted biomarker for B[a]P exposure. This high level of sensitivity and robustness of the method was demonstrated in a study of B[a]P metabolic profiles in human bronchoalveolar H358 cells induced or uninduced with the AhR ligand, 2,3,7,8-tetrachlorodibenzodioxin (TCDD). All the signature metabolites were detected and successfully quantitated. Our results suggest that all three metabolic pathways contribute equally in the overall metabolism of B[a]P in H358 cells with or without TCDD induction. The sensitivity of the method should permit the identification of cell-type differences in B[a]P activation and detoxication and could also be used for biomonitoring human exposure to PAH.